REGULASI EMOSI PADA ORANGTUA YANG MEMILIKI ANAK CERDAS ISTIMEWA - Nurhera, Nurhera (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2012)
AbstractThe purpose of this research was to determine the dynamics of self-conceptat the beginning of adult child abused victim and the impact of self-concept onbehavior in the community. Subject of the research is 2 adult male and femalewho have been victims of child abused . Data collection techniques in this studywas conducted using semi-structured interviews, non-participant observationand graphic tests (BAUM, DAP, HTP).Data analysis was done in this research using is content analysis (contentanalysis) is a method of analysis used in this research to describe the dynamicsof self-concept at the beginning adult child abused victims. The approach usedin this research is defined as a case study of the case is the case of a phenomenonthat is present in a limited context. The case may be individuals, small groups,roles, communities, and even a country.The results of this research indicate that after receiving a child abusedtwo subjects had low confidence but after a subject growing up, self-conceptis formed on both subjects are positive self-concept. Positive self-concept isformed the support and motivation of others (friends), awareness of spiritualitysuch as prayer and multiply prayers, and always take lessons from what hashappened. The impact of a positive self concept makes better relationshipswith the community and the subject easier to get along with other people.Keywords : Self-Concept, Adult, Child Abused